Universal health coverage and key populations. Issue 5 (September 2019) - Macdonald, Virginia; Verster, Annette; Seale, Andrew; Baggaley, Rachel; Ball, Andrew
Abstract : Purpose of review: There is renewed focus at global and national level to adopt commitments to ensure universal access to health services. The present study highlights key considerations to ensure that the commitment to 'leave no one behind' includes key populations, recognizing the specific impact of marginalization, stigma, discrimination, and criminalization on their access to health. Recent findings: Universal health coverage (UHC) means that all people can use the promotive, preventive, curative, rehabilitative, and palliative health services they need, of sufficient quality to be effective, while also ensuring that the use of these services does not expose the user to financial hardship. Countries commit to UHC through Sustainable Development Goals (SDG Target 3.8 Achieve universal health coverage, including financial risk protection, access to quality essential health-care services and access to well tolerated, effective, quality, and affordable essential medicines) . Summary: UHC cannot be achieved without addressing the needs of key populations. At the same time, the goal of UHC provides new opportunities to improve health equity and the health of key populations. Political commitment, defining and including essential high-impact, evidence-based interventions for key populations, and their full integration into national health benefit packages; integrated, decentralized, and differentiated health services with involvement, ownership, and acceptance of communities to ensure equity and quality; ensuring financing for UHC provides coverage for key populations, including those who may be undocumented, are needed. Developing more effective interventions and service delivery approaches, providing a supportive policy and legal environment; and measuring progress against clear targets for accountability and programme adjustment will also be required for key populations to benefit fully from UHC.